Analisa Kapasitas Embung Untuk Suplai Air Irigasi (Studi Kasus : Desa Sendayan , Kecamatan Kampar Utara) - Irpan, Apdani; Sujatmoko, Bambang; Hendri, Andy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The problem of lacking of water for agricultulal irrigation in the dry season is a problem happened in Sendayan Village, North Kampar District, Kampar Regency. To solve this problem, the construction of pond in form of detention pond is planned. The capacity of detention pond is determined by doing an analysis of water availability, that is dependable flow method of FJ.Mock and the water required of irrigation, so that from both analysis mentioned before, it will be got a condition of water balance, that will show the months of lacking water. The result of research shows that the water required of irrigation on maximum condition is 0,210 m3/second in May and for the maximum dependable flow is 0,547 m3/second in December. If it is related with the discharge of water required of irrigation with the availability of water, so it will be appeared that the months when water lacks (February, June, Juli, August, September and October) and the months when maximum lacking of water happened on second period of June that is 0,139 m3/second. The capacity of detention pond for the gate operation time of 4, 5, and 6 hours is 8,24 hectare, 10,30 hectare, and 12,36 hectare with the depth of detention pond is 2 metre and the wide of farm irrigated is only 1,90 hectare, so that the analysis of storage capacity of detention pond with the existing area is 1,90 hectare and the depth of detention pond is 2 metre carried out so that the result shows that the wide of farm which can be irrigated for the gate operation time of 4, 5, and 6 hours is 93,1 hectare, 88,1 hectare, and 85 hectare. Key word : detention pond, dependable flow, capacity of detention pond, water required, lack of water.